Sulfate removal rate and metal recovery as settling precipitates in bioreactors: Influence of electron donors - Costa, Rachel Biancalana [UNESP]; Gouvea Godoi, Leandro Augusto; Maluf Braga, Adriana Ferreira; Delforno, Tiago Palladino; Bevilaqua, Denise [UNESP] (Elsevier B.V., 2021)
Four down-flow structured bed bioreactors were operated targeting biological sulfate-reduction and metal recovery. Three different electron donors were tested: glycerol (R1), lactate (R2), sucrose (R3), and a blend of the previous three (R4) with an increasing copper influent load (5, 15, and 30 mg Cu2+.L-1). Copper inhibited sulfate-reduction in R1 (15 mg Cu2+.L-1) and R3 (5 mg Cu2+.L-1), but the fermentative activity was not affected. R2 and R4 were not inhibited by the copper influent concentration. R2 provided the highest sulfate reduction rate (1767.3 +/- 240.1 mg SO42-.L.day(-1)). Nonetheless, the accumulation of settling precipitates was 22 % higher in R4 than in R2, indicating the former yielded the highest metal recovery as settling precipitates (24.8 g FSS.L-1, 25 % Fe2+, 5% Cu2+). 16S rRNA sequencing showed highest diversity of sulfate-reducing bacteria in R2. A predominance of sulfate-reducing and fermentative bacteria with more similarity was observed between microbial populations in R1 and R4, despite the difference in toxicity thresholds. Hence, the electron donor influenced not only the biological sulfate reduction, but also metal toxicity thresholds and metal recovery as settling precipitates.
Keywords: Acid mine drainage; Sulfidogenenis; 16 rRNA sequencing; Copper toxicity; Metal precipitation; Down-flow structured-bed reactors